Is it posible to be historical without being historian? (Devenires, 2009)
This paper aims at an analysis of the notions of “being historic” (or “being historical”) and “being historicist” as two interdependent and contradictory stances by which modern subjects come into terms with historical knowlegde and time. Firstly (1-6), I analyze both notions from Nietzsche on. “Being historic” refers to the temporality of human being, her exposition to time and the contingency of actions, whereas “historicist” is supossed to mean objectivity and fidelity in reconstructing the past times. Then (7-8) I analyze how this relationship has been transformed in the present times. Drawing on Hans Ulricht Gumbert, I examine how a new demand for history coexists with a desire for inmediate, sensible experience of the things past, as we have a new perception of time which might well be called “new simmultaneity”. In the end, I argue for a more immediate historical knowledge and en notion of “being historic” freed from spaciality.
Keywords: historical; historicist; Nietzsche; Hans Ulrich Gumbrecht